Transcriptome analysis reveals pathogenesis-related gene 1 pathway against salicylic acid treatment in grapevine (Vitis vinifera L) - Rahman, Faiz Ur; Khan, Irshad Ahmad; Aslam, Ali; Liu, Ruitao; Sun, Lei; Wu, Yandi; Aslam, Muhammad Muzammal; Khan, Asad Ullah; Li, Peng; Jiang, Jianfu; Fan, Xiucai; Liu, Chonghuai; et al. (Frontiers in Genetics, 2022)
Salicylic acid (SA) is a well-studied phenolic plant hormone which plays an important role in plant defense against the hemi-biothrophic and biothrophic pathogens that depends on the living cells of host for the successful infection. In this study, the pathogenesis test was performed between ‘resistant’ Vitis davidii and ‘susceptible’ V. vinifera plants against grape white rot disease (Coniothyrium diplodilla). It was found that SA contents were found higher in resistant grape cultivar after different time points. So, RNA-seq analysis was conducted on susceptible grapevine cultivar after 12, 24 and 48 h of SA application with the hypothesis that SA may induce defense genes in susceptible cultivar. A total 511 DEGs were identified from the RNA-seq data including some important genes WRKY1/2, NPR1, TGA2 and PR1 for SA defense pathway. DEGs related to phytohormone signal transduction, and flavonoid biosynthetic pathways were also upregulated. The quantitative Real-Time PCR (qRT-PCR) results of the significantly expressed transcripts were found consistent with the transcriptome data with high correlation between the two analyses. The pathogenesis-related gene 1 (PR1) was selected for further promoter analysis because it is the important marker gene for plant defense. The promoter sequence showed that it contains some important cis-elements (W-box, LS7, as-1, and TCA-element) to recruit the transcription factor (WRKY, NPR1 and TGA2) to express the VvPR1 gene in response to SA treatment. The VvPR1 promoter was serially deleted into different fragments (-1837, -1443, -1119, -864, -558, -436, and -192,) and constructed a vector with GUS reporter gene. Deletion analysis revealed that the VvPR1 promoter between -1837 bp to -558 bp induced significant GUS expression with respect to mock. On the Base of these results, the -558 bp region was assumed to be an important part of the VvPR1 promoter. In this research, we expanded the available information regarding SA induced defense in susceptible grapes and recognized the molecular mechanisms through which this defense might be mediated.